2019
DOI: 10.1186/s42397-019-0024-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on seed protein characteristics in eight lines of two Gossypium species

Abstract: Background: In order to achieve the targets aiming at the improvement of protein quality, knowledge regarding seed protein fractions and polypeptides constituting them in different crops is essential. Besides having high nutritional value as animal feed and human food, the protein isolates from cottonseed meal have also been proven promising as industrial raw materials for a number of applications. As far as Indian work on the characterization of cotton seed proteins is concerned, relatively meagre reports are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Singh and Kaur (2019) reported that polypeptides in the range of molecular weight of 12−120 kDa and 11.5−122 kDa correspond to albumin and globulin (salt‐soluble) fractions, respectively. SDS‐PAGE pattern of GPI in the research of Feyzi et al (2018) showed higher molecular weight peptides in freeze‐dried samples (range: 20−140 kDa) compared with vacuum oven dried.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Singh and Kaur (2019) reported that polypeptides in the range of molecular weight of 12−120 kDa and 11.5−122 kDa correspond to albumin and globulin (salt‐soluble) fractions, respectively. SDS‐PAGE pattern of GPI in the research of Feyzi et al (2018) showed higher molecular weight peptides in freeze‐dried samples (range: 20−140 kDa) compared with vacuum oven dried.…”
Section: Resultsmentioning
confidence: 99%
“…Also, there were no subunits of ~27 and ~32 kDa after freeze-drying, while subunits of around 32 kDa might be attributed to phytohemagglutinin, a common antinutritional agent in beans. Singh and Kaur (2019) reported that polypeptides in the range of molecular weight of 12−120 kDa and 11.5−122 kDa correspond to albumin and globulin (saltsoluble) fractions, respectively. SDS-PAGE pattern of GPI in the research of Feyzi et al (2018) showed higher molecular weight peptides in freeze-dried samples (range: 20−140 kDa) compared with vacuum oven dried.…”
Section: Sds-pagementioning
confidence: 99%
“…In another study, out of 4 protein fractions, globulins reached a maximum (33-63.7%), followed by albumins (20.8-32.2%), glutelins (9.1-28%), and prolamins at the lowest concentration (Singh & Kaur, 2019). The molecular weights of polypeptides in cottonseed protein from Gossypium arboreum and Gossypium hirsutum lines were found to be in the range of 10-122 kDa (Singh & Kaur, 2019). The molecular weight of the alkali-soluble protein fraction varied from 10-54 kDa in both species.…”
Section: Molecular Weightmentioning
confidence: 87%
“…These protein subunits include both salt-(globulins 5S: 24 and 22 kDa) and water-soluble fractions (albumins; albumin 2S: 20, 15 and 14 kDa) (Sun et al, 2012). In another study, out of 4 protein fractions, globulins reached a maximum (33-63.7%), followed by albumins (20.8-32.2%), glutelins (9.1-28%), and prolamins at the lowest concentration (Singh & Kaur, 2019). The molecular weights of polypeptides in cottonseed protein from Gossypium arboreum and Gossypium hirsutum lines were found to be in the range of 10-122 kDa (Singh & Kaur, 2019).…”
Section: Molecular Weightmentioning
confidence: 93%
“…The molecular weight changes with maturation [49]. Recently, Singh et al [50] applied one-and two-dimensional gel electrophoresis to explore the cottonseed protein characteristics. They compared the relative distribution of four protein fractions (i.e., albumins, globulins, prolamins and glutelins) of cottonseed in eight lines of two Gossypium species and found that globulins represented the dominating fraction in both species followed by albumins, glutelins and prolamins.…”
Section: Composition and Molecular Weightmentioning
confidence: 99%